How Can Critical Reflection Improve Social Work Practice with Children and Families? - Morley, Christine; Marshall, Lee; Leggatt-Cook, Chez (The British journal of social work, 2023)
Abstract The impacts of neoliberal managerialism mean that practitioners working in child protection programmes are often challenged to balance social work values, with formal compliance activities to reduce risk. Within this context, what are the possibilities for practitioners to creatively navigate complex practice environments to achieve better outcomes for children and families? And how might transformative research empower practitioners to improve practice by reconnecting their work with the emancipatory values of the profession? This article seeks to address these questions by showcasing key findings of a state-wide study focused on empowering children’s voices, through the presentation and analysis of a case study. The research used a pre-test/post-test design with critical reflection as a methodology to transform the practice of front line workers and managers who work with children and families in an Australian-based non-government organisation. The case study illustrates the conceptual and practical processes involved in achieving change in a way that can be replicated by others and transferred to other contexts. The findings of the research suggest that critical reflection can be effective to enable practitioners to improve practice with children and families. The article concludes by highlighting implications for organisations in supporting critically reflective practitioners. The article explores how to improve social work practice with children and families. Due to changes in policy in recent decades, some practitioners have become preoccupied with managing risk in a way that can hinder their capacity to build genuinely supportive relationships with children and families. The article reports on research that employed critical reflection, which is a form of self-analysis, as both an educative and potentially transformative methodology, to reprioritise social justice issues in practice. The research involved a state-wide study with an Australian-based, non-government organisation and focused on empowering children’s voices. The findings present and analyse a case study from the research to compare changes in one practitioner’s thinking and practice, before and after she critically reflected on said practice. The reflective process demonstrated by the practitioner is presented in a way that can be replicated by others and transferred to other contexts. The findings of the research suggest that critical reflection can be effective to enable practitioners to improve practice with children and families. The article concludes by highlighting implications for organisations in supporting critically reflective practitioners.